2020
DOI: 10.14689/enad.25.4
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of the Mothers to Cope with the Problem Behaviors of the Children with Special Needs during Coronavirus (COVID-19) Process

Abstract: Experiences of the mothers to cope with the problem behaviors of the children with special needs during coronavirus (COVID-19) process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 14 publications
1
8
0
3
Order By: Relevance
“…Especially individuals with severe disabilities were able to benefit less from the support provided at home. A similar study conducted in Turkey (Karahan et al, 2021) examined mothers' experiences concerning their children with special needs and findings were obtained that support the results of the present study. In the aforementioned study mothers asserted that the fact their children were away from school and their peers led to some problems and that they failed to make pedagogic and material adaptations and encountered drawbacks in preparing or designing Haziran 2023 Cilt 25 Sayı 1 (97-120) equipment for their children.…”
Section: Support Resourcessupporting
confidence: 90%
See 3 more Smart Citations
“…Especially individuals with severe disabilities were able to benefit less from the support provided at home. A similar study conducted in Turkey (Karahan et al, 2021) examined mothers' experiences concerning their children with special needs and findings were obtained that support the results of the present study. In the aforementioned study mothers asserted that the fact their children were away from school and their peers led to some problems and that they failed to make pedagogic and material adaptations and encountered drawbacks in preparing or designing Haziran 2023 Cilt 25 Sayı 1 (97-120) equipment for their children.…”
Section: Support Resourcessupporting
confidence: 90%
“…Moreover, the finding that isolated life at home increased the duration of watching TV and using mobile devices (Chen et al, 2020;Karahan et al, 2021) supports the view that the screen exposure time increased, which is one of the effects of Covid-19 on social life. Especially mothers indicated that in the pandemic process their children lost the routines and social environment that they used to have in the pre-COVID-19 period and that they have difficulty in dealing with children's problem behaviors that emerge as a result of the increase in the duration of staying indoors and that they feel lonely (Karahan et al, 2021).…”
Section: Support Resourcesmentioning
confidence: 53%
See 2 more Smart Citations
“…When the literature on this field is considered, it can be seen that there is an emphasis on the fact that emergency online education has negative effects on inclusive students. According to the results of the interviews with the parents of inclusive students, it was found that the psycho-social problems of the students increased, there were problems related to technological infrastructure and technology use and that this situation caused injustice in education (Başaran, Doğan, Karaoğlu & Şahin, 2020;Karahan, Yıldırım, Demiröz, Kaya & Kayhan, 2021). Furthermore, when the related studies were examined, it was found that there have not been enough applications in terms of inclusive education; necessary materials for students have not been available; the individualized education plans could not been adapted to online education and not enough attention has been paid to training the parents (Karasel-Ayda, Bastas, Altinay, Altinay &Dagli, 2020; Greenway & Eaton-Thomas, 2020).…”
Section: Introductionmentioning
confidence: 99%